Social media in higher education case studies, reflections and anlysis - Rowell, Chris; Open Book Publishers (Open Book Publishers, 2019)
"How does social media affect working life in Higher Education? How are universities harnessing its power to aid student learning? This innovative collection brings together academics and those working in professional services to examine these questions and more. The diverse and expert contributors analyse the many ways social media can be used to enhance teaching and learning, research, professional practice, leadership, networking and career development. The impact of social media is evaluated critically, with an eye both to the benefits and the problems of using these new forms of digital communication. This is the first volume to give such detailed attention to this area of high interest. Its innovative approach extends to its creation, with contributors found via their presence on Twitter. The short and impactful chapters are accessible while retaining an academic focus through their application of relevant learning theories and educational context. Social Media and Higher Education is essential reading for any professional working in higher education, including lecturers teaching education courses. It is also significant for researchers looking at more recent developments in the field and what it means to work in a modern higher education environment."--Publisher's website.
Acknowledgements -- Contributors -- Part One. Introduction. 1. From a Tweet to a Blog, to a Podcast, to a Book / Chris Rowell ; 2. Social Media in Higher Education - The Podcast / Chris Rowell -- Part Two. Professional Practice. 3. Developing a Professional Online Presence and Effective Network / Sue Beckingham ; 4. Re-Engineered CPD and Modelled Use of Cloud Tools and Social Media by Academic Developers / Martin Compton and Timos Almpanis ; 5. Ten Days of Twitter / Mark Warnes ; 6. Open and Networked Scholarship / Suzan Koseoglu -- Part Three. Teaching and Learning. 7. Exploring the Use of Social Media in the Higher Education Classroom / Alex Avramenko and Chrissi Nerantzi ; 8. The Use of Social Media Tools and Their Application to Creative Students / Serena Gossain ; 9. Role of Social Media in Learning: Benefits and Drawbacks - How Social Presence Theory Explains Conflicting Findings Paul Kawachi Bursting Out of the Bubble: Social Media, Openness and Higher Education Jennie Blake, Chris Millson and Sam Aston Cambridge Analytica, Facebook, and Understanding Social Media Beyond the Screen / Zoetanya Sujon -- Part Four. Leadership. 12. Leadership and Social Media / Julie Hall ; 13. Leadership and Social Media: Challenges and Opportunities / Donna M. Lanclos and Lawrie Phipps -- Part Five. Building Networks. 14. Building Cohort Identity through Social Media / David Webster ; 15. Creating a Sense of Belonging and Connectedness for the Student Arrival Experience in a School of Arts and Humanities / Rachel Challen ; 16. Joint Reflection on Twitter, Phenomenography and Learning Friendships / Margy MacMillan and Chrissi Nerantzi ; 17. PressEd - Where the Conference Is the Hashtag / Pat Lockley -- Part Six. Innovation. 18. Expertise in Your Ears; Why You Should Jump on the Podcasting Bandwagon / Dave Musson ; 19. Etiquette for the Anthropocene / Jane Norris ; 20. Learning to Twalk: An Analysis of a New Learning Environment / Andrew Middleton ; 21. Academics' Understanding of Learning Spaces: Attitudes, Practices and Outcomes Explored through the Use of Social Media / Santanu Vasant -- Part Seven. The Personal Journey. Somewhere in Between: My Experience of Twitter as a Tool for Continuous Personal Development / Andy Horton ; 23. The 'Healthy Academic', Social Media, and a Personal and Professional Journey / Neil Withnell -- Glossary -- List of Illustrations -- Index.
Available through Open Book Publishers.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Keywords: Education, Higher -- Computer network resources; Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on; Internet in higher education; Social media in education